Dynamics indicators of supporting-spring properties of a foot in the children of primary school age with derivation of hearing during process of adaptive physical education under influence of author's technology on prevention of violations - Vitaliy Kashuba; Dmitriy Afanasiev (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Dynamics indicators of supporting-spring properties of a foot in the children of primary school age with derivation of hearing during process of adaptive physical education under influence of author's technology on prevention of violations the biomechanical properties of foot Abstract The global trend of increasing number of people with special needs encourages the scientific community to search effective pedagogical methods and techniques aimed at mobilizing all compensatory opportunities that will contribute to the successful socialization of students with hearing impairments at the present stage. Objective. In general, number of respondents involved in the sequential conversion phase of the experiment reflected on the children of 7 years old (n=37). Methods. In the given research uses: analysis of professional scientific and methodological literature, pedagogical observation; anthropometry, photometry. In the determining somatotype by W.H. Sheldon (digestive, muscular, thoracic, asthenoid) main attention was focused on the development and ratio of such features as a shape of back, chest, abdomen, legs, the amount of development a bone, muscle and adipose tissue. Tables of M.O. Friedland were used to estimate height of the foot arch by the methods of mathematical statistics. Results of the study. Technology of prevention violations of biomechanical properties of foot in the children of primary school age with deprivation of sensory systems in the process of physical education is based on the following structural components: organizational, diagnostic, methodological, control and correctional, informational and effective. Technology includes the following stages: preparatory, basic, supporting. The study dynamics of support-spring properties of foot in children of 7 years old with hearing derivation under the influence of author's technology showed that in the boys rate of increase of a foot length exceeded rate of increase of a foot length in the girls. Generally, average rate in the boys increased on 3.02% (from (178.97; 4.37) to (184.38; 4.07) mm), and in the girls a median value increased on 2.81% (from (178.28; 175.66; 193.88) to (183.28; 180.66; 198.88) mm). Conclusions. Results of a sequential conversion experiment confirmed effectiveness of a developed technology. Regardless the type of physique in children of both sexes there was an improvement of the support-spring properties of a foot, i.e. after implementation of a proposed author's technology had a positive effect on the children with hearing deprivation in all types of body structure. Distribution of children with hearing derivation by the size of foot arch according to the stage of research showed that after the experiment a share of boys with normal feet by the angle of arch increased on 40.9 and the girls - on 53.3%. Regarding the distribution of children with hearing derivation by value of a Friedland podometric index, at the end of experiment, percentage of boys with normal feet increased on 40.9, and the girls - on 46.7%.